Analisis Kebijakan dan Kepimpinan Keselamatan dan Kesehatan Kerja pada Kejadian Kecelakaan Kerja di Rumah Sakit Umum X Kabupaten Y - Ekin Akhsa Febriandini; Sri Hernawati; Isa Ma’rufi (Multidisciplinary Journal, 2019)
The regulation of Manpower no 5 Year 1996 on Safety Management System and Occupational Health Article 3 explains several points including the policy establishment for Safety Management System and Occupational Health. The commitment and the policy in the work place should be reviewed repeatedly and regularly. The recurring and regular review are expected to improve the performance of Safety and Occupational Health in the work place. This research aims at analyzing the policy and the leadership in K3 (Safety and Occupational Health) on Occupational Accident in X Hospital in Y Regency. The methodology includes quantitative analysis employing cross sectional research design. The data were collected by questionnaires. This research uses Chi Square with significance of 0,05 or ɑ=95%. Sampling consists of 83 respondents. The finding indicates that there is no correlation between the policy and the leadership in Safety and Occupational Health with Occupational Accident in X General Hospital in Y Regency. The hospital management should concerns more on constructing and developing Safety and Occupational Health Unit in the hospital.Keywords: policy, leadership, safety and occupational health, occupational accident, hospital